Availability of Hydrogen Shapes the Microbial Abundance in Biofilm Anodes based on Geobacter Enrichment. Issue 18 (21st July 2020) - Korth, Benjamin; Kuchenbuch, Anne; Harnisch, Falk
Abstract: Biofilm anodes based on Geobacter enrichment in one‐chamber and two‐chamber reactors are qualitatively and quantitatively investigated. The methanogenic community of biofilms in both types of reactors consists exclusively of hydrogenotrophs, mainly the genus Methanobacterium . As qPCR demonstrates in one‐chamber reactors, the abundance of Geobacter and methanogens increases due to the presence of cathodically produced hydrogen. In two‐chamber reactors, the abundance of methanogens is decreased by 98 % compared to one‐chamber reactors. Adding hydrogen gas to the anodic compartment of two‐chamber reactors recovers the abundance of methanogens and Geobacter . Ratios of methanogens/bacteria are confirmed by using the cofactor F420 autofluorescence of methanogens. The impact of the reactor setup for developing primary microbial electrochemical technologies is discussed, reasoning that two‐chamber reactors have to be generally favored. Yet, their use inheres a trade‐off when cultivating biofilm anodes, as the indicated syntrophic interactions between methanogens and Geobacter are reduced, but pH decrease might influence microbial processes. Abstract : Beaming with joy : The presence of hydrogen increases the abundance of both Geobacter and methanogens in biofilm anodes, thus communities shine "in the dark" based on F420 cofactor of methanogens. Microbial composition is verified with qPCR and genetic fingerprinting showing a higher degree of purity of Geobacter enrichment biofilms in two‐chamber reactors compared to one‐chamber reactors that is offset by a lower cell number of Geobacter .